Regulation of Ghrelin Receptor by Periodontal Bacteria in Vitro and in Vivo - Nokhbehsaim, Marjan; Damanaki, Anna; Nogueira, Andressa Vilas Boas [UNESP]; Eick, Sigrun; Memmert, Svenja; Zhou, Xiaoyan; Nanayakkara, Shanika; Götz, Werner; Cirelli, Joni Augusto [UNESP]; Jäger, Andreas; Deschner, James (Hindawi, 2017)
Ghrelin plays a major role in obesity-related diseases which have been shown to be associated with periodontitis. This study sought to analyze the expression of the functional receptor for ghrelin (GHS-R1a) in periodontal cells and tissues under microbial conditions in vitro and in vivo. The GHS-R1a expression in human periodontal cells challenged with the periodontopathogen Fusobacterium nucleatum, in gingival biopsies from periodontally healthy and diseased individuals, and from rats with and without ligature-induced periodontitis was analyzed by real-time PCR, immunocytochemistry, and immunofluorescence. F. nucleatum induced an initial upregulation and subsequent downregulation of GHS-R1a in periodontal cells. In rat experimental periodontitis, the GHS-R1a expression at periodontitis sites was increased during the early stage of periodontitis, but significantly reduced afterwards, when compared with healthy sites. In human gingival biopsies, periodontally diseased sites showed a significantly lower GHS-R1a expression than the healthy sites. The expression of the functional ghrelin receptor in periodontal cells and tissues is modulated by periodontal bacteria. Due to the downregulation of the functional ghrelin receptor by long-term exposure to periodontal bacteria, the anti-inflammatory actions of ghrelin may be diminished in chronic periodontal infections, which could lead to an enhanced periodontal inflammation and tissue destruction.